Evaluasi Efektivitas Corporate Social Responsibility Pada PT Semen Tonasa - Arianto Taliding (STIM-LPI Makassar, 2021)
The purpose of this research was to evaluate the effectiveness of Corporate Social Responsibility (CSR) in PT Semen Tonasa. In this research, researchers based on a case study in PT Semen Tonasa (Biring Ere village, Pangkep District, South Sulawesi). The data obtained with interview and documentation method. Data analysis was performed with descriptive analysis, interpretative, and comparative method. The analysis show that implementations of CSR PT Semen Tonasa on 2017-2019 had been effectively by looking at comparisons between CSR program and CSR realization, as well as results of interview with related parties. The implications of this research is expected to PT Semen Tonasa make CSR as a sustainable program for welfare of firm and people.